2016
DOI: 10.1177/0003319715617074
|View full text |Cite
|
Sign up to set email alerts
|

Serum Potassium Levels and Short-Term Outcomes in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: Current guidelines recommend maintaining serum potassium levels between 4.0 and 5.0 mEq/L (1 mEq/L = mmol/L) in patients with acute myocardial infarction. However, these guidelines are based on studies conducted before the β blocker and reperfusion era. We retrospectively analyzed 6613 patients diagnosed with ST-segment elevation myocardial infarction (STEMI) who presented without renal insufficiency. Patients were categorized into 5 groups according to mean serum potassium levels: <3.5, 3.5 to <4.0, 4.0 to <4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…We compared the clinical characteristics of hospital survivors and non-survivors, and found that some of laboratory tests were associated with hospital outcomes, such as RDW and potassium. These findings are partially consistent with previous reports (4)(5)(6)(7)(8)(9)(10)(11). However, we noted that percentages of basophil and eosinophil were decreased in hospital non-survivors, suggesting that eosinophil and basophil percentages are potential prognostic factors for AMI and thus unmasking a potential (new) of these blood cells in the complications of acute coronary syndrome.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We compared the clinical characteristics of hospital survivors and non-survivors, and found that some of laboratory tests were associated with hospital outcomes, such as RDW and potassium. These findings are partially consistent with previous reports (4)(5)(6)(7)(8)(9)(10)(11). However, we noted that percentages of basophil and eosinophil were decreased in hospital non-survivors, suggesting that eosinophil and basophil percentages are potential prognostic factors for AMI and thus unmasking a potential (new) of these blood cells in the complications of acute coronary syndrome.…”
Section: Discussionsupporting
confidence: 93%
“…For example, higher red blood cell distribution width (RDW) (4), neutrophil to lymphocyte ratio (5), mean corpuscular volume (MCV) (6), platelet count (7) and white blood cell (WBC) (8) count are associated with poorer outcomes in patients with acute myocardial infarction (AMI), while decreased Focus on State of the Art in Diagnostics of the Acute Coronary Syndrome hemoglobin is associated with higher mortality (9). In addition, serum potassium level can also impact the outcomes of AMI patients (10,11). Since these routine laboratory tests are usually mutually correlated (e.g., WBC and RDW (12), RDW and hemoglobin (12), platelet count and potassium (13), platelet count and RDW (14), neutrophil count and RDW (15), the confounding effects of another tests cannot thus be ignored when the prognostic value of an interesting test is evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In three out of six studies that provided a detailed classification of SPCs, patients with SPC between 3.5 and less than 4.0 mEq/L showed the lowest, unadjusted short-term mortality risk. 9,15,16 In the study by Choi et al 10 and Ma et al 19 patients with a SPC of 3.5 to less than 4.0 mEq/L and patients with a SPC of 4.0 to less than 4.5 mEq/L had a similar risk of dying. In contrast, Keskin et al 28 found a slightly higher inhospital mortality (3.7%) in patients with a SPC of 3.5 to less than 4.0 mEq/L than in patients with a SPC of 4.0 to less than 4.5 mEq/L (3.1%).…”
Section: Short-term Mortalitymentioning
confidence: 94%
“…[9][10][11] Moreover, results from available studies investigating the consequences of hypokalemia were conflicting. Hypokalemia was found to be associated with VA 9,[12][13][14][15][16] and higher mortality 9,10,15 in some studies, whereas others did not find increased risks for VA 10,[17][18][19] or mortality 11,16,19 in patients with AMI.…”
Section: Hypokalemiamentioning
confidence: 99%
“…1 To our knowledge, these recommendations have not been revised, since in formal guidelines and in the most recent guidelines, this issue is not mentioned directly and only the undetermined role or possible deleterious effects of glucoseinsulin-potassium (GIK) infusions are discussed. 9,10 Ma et al, 11 in this issue of Angiology, retrospectively evaluated short-term outcomes of 6613 patients presenting with STEMI, without renal insufficiency, according to K levels at presentation. Following adjustments to potential confounders, the authors found a J-shaped relationship between patient outcomes and K levels, with lowest predefined event rate with K levels of 4 to 4.5 mEq/L.…”
mentioning
confidence: 99%